The Book of the Twelve and the new form criticism - Boda, Mark J.; Floyd, Michael H.; Toffelmire, Colin M. (Ancient Near East monographs, 2015)
"Contributors to this volume explore the theoretical issues at stake in recent changes in form criticism and the practical outcomes of applying the results of these theoretical shifts to the Book of the Twelve. This volume combines self-conscious methodological reflection with practical examination of specific texts in an effort to demonstrate the practical consequences of theoretical decisions and the value of certain methodological stances"--